2020
DOI: 10.3390/ijerph17217704
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal Ferritin Levels during Pregnancy and ADHD Symptoms in 4-Year-Old Children: Results from the INMA–INfancia y Medio Ambiente (Environment and Childhood) Prospective Birth Cohort Study

Abstract: Ferritin status during prenatal brain development may influence the risk of attention deficit and hyperactivity disorder (ADHD) symptoms in childhood. We investigated the association of maternal ferritin in pregnancy and ADHD-like symptoms in offspring. A total of 1095 mother-child pairs from three birth cohorts of the INMA Project (Spain) were studied. Maternal plasma ferritin in pregnancy was measured at 11.57 weeks of gestation. Children′s ADHD-like symptoms at ages 4–5 years were assessed using the ADHD Ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 76 publications
(84 reference statements)
3
18
0
Order By: Relevance
“…Of these, 142 papers were fully read and led to the identification of 41 studies meeting the inclusion criteria. Scanning reference lists led to the inclusion of three more studies, resulting in a total of 44 studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 142 papers were fully read and led to the identification of 41 studies meeting the inclusion criteria. Scanning reference lists led to the inclusion of three more studies, resulting in a total of 44 studies [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ] ( Figure 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Maternal measurements were timed throughout pregnancy, with most of them occurring during the third trimester or at birth. Of the 10 studies that examined the first trimester of pregnancy, reflecting the period of organogenesis, only four explored outcomes beyond infancy [ 53 , 58 , 60 , 64 ]. One found impaired memory in 5-year-old children of mothers with anorexia nervosa and low ferritin levels [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Maternal obesity was a confounder in this meta-analysis as the majority of studies did not adjust findings by BMI, or other major confounders such as glycaemic control or gestational morbidities. Only one study adjusted data for weight gain during pregnancy [ 30 ], two studies adjusted data for birth weight and gestational age [ 15 , 19 ], and three studies adjusted for education level [ 12 , 20 , 28 ], thus, reported motor scores can be considered as independent of those confounders.…”
Section: Discussionmentioning
confidence: 99%
“…This may relate to the fact that GDM often involves a less severe form of hyperglycaemia of shorter duration. We noted that two studies were limited to women with pre-existing diabetes and had the largest difference in motor scores between groups [ 12 , 32 ], whereas studies limited to GDM [ 28 , 30 ] had the lowest difference between groups. In the study by Torres-Espinola et al [ 30 ], children born to diabetic mothers had the lowest motor skill at 18 months, but this difference was lost in adjusted models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation